STRENGTHENING INSTITUTIONS FOR SUSTAINABLE LAND MANAGEMENT IMPLEMENTATION - EVIDENCES FROM HOA BINH AND QUANG TRI PROVINCES - Thi Thu Ha, Tran; Minh Thanh, Nguyen (Journal of Forestry Science and Technology, 2017)
Agricultural land use in Vietnam is taken by millions of farmer households from upland to coastal areas and land degradation is a serious problem with 7.6 million hectares of land degraded. Under land degradation issues from different regions, there is a range of sustainable land management (SLM) programs undertaken by different institutions from governmental to international, national and local non-governmental organizations. In this context, the inner-agency capacity and interagency collaboration are very important for SLM effectively implementation. The study assessed SLM programs and institutions, examined institutional obstacles to SLM implementation in the selected study sites, and recommended policies and measures that aims to improve the implementation of SLM initiatives. The results show that there are a number of institutional challenges that hindering Vietnamese farmer’s adoption of SLM practices. The policy recommendations therefore focus on solving three main aspects as capacity building for extension services and other SLM implementers, revising financial mechanism for SLM supports and, improving institutional structures of SLM implementation from central to local levels.